Progressively providing ionic inhibitor via functional nanofiber layer to stabilize lithium metal anode. (10th April 2019) - Hu, Mengfei; Yuan, Yuan; Liu, Yajing; Tian, Liying; Zhang, Yayun; Long, Donghui
Abstract: Lithium metal batteries are the most potential candidate for rechargeable batteries today to meet the urgent demands for high energy density. However, uncontrolled dendrite formation and infinite volume expansion hinder the practical application of lithium metal anode. Herein, we develop a new strategy to make physical accommodation and chemical ionic intervention well-combined to modulate the Li deposition behavior. A K + -doped nanofiber protective layer, having abundant lithophilic groups and porous framework is electrospun on current collector. It can provide high affinity with electrolyte and uniform pathway for lithium ions transportation, and a host for the volumetric change during lithium plating/stripping. Moreover, it can gradually release K + as an inhibitor to contribute to more stable SEI layer and prevent aggregation of Li ions by forming an electrostatic shielding on the surface of electrode. As a result, the functional K + -doped nanofiber protective layer can guide uniform lithium deposition, leading to high Coulombic efficiency (98.5%) and low overpotential (∼15 mV) in symmetric cells with long lifespan. This work sheds the dawn of the research on the multi-functional protective layer material for dendrite-free lithium metal batteries.